German Radioactive Waste Changes in Policy and Law - Rybski, Robert (Routledge Focus on Environment and Sustainability, 2022)
This book presents the universal issue of radioactive waste management from the perspective of the German legal system, analysing how lawmakers have responded to the problem of nuclear waste over the course of the last seventy years. In this book, Robert Rybski unwraps and explains the perplexing legal and social issues related to radioactive waste. He takes readers through the entire 'life-cycle': from the moment that radioactive material is classified as radioactive waste, through to the period of interim storage, and right up to its final disposal. However, this last step in radioactive waste management (that of final disposal) has not yet been achieved in Germany, or anywhere in the world, and has been the subject of hefty public debate for dozens of years. As a result, the book analyses the most recent regulations in place to enable final disposal. This book will be of interest to energy policy experts, academics and professionals who work in the area of nuclear energy.